The changing role of the marketing researcher in the age of digital technology: Practitioner perspectives on the digitization of marketing research. (January 2020) - Cluley, Robert; Green, William; Owen, Richard
After years of hype, marketing researchers are now facing the challenge of integrating new digital technologies into their work. Based on an analysis of 44 key informant interviews with marketing research practitioners, the study develops a framework to describe the main benefits and challenges of digital technologies in marketing research, as perceived by marketing researchers themselves. It highlights successful strategies that have been employed to exploit digital technologies and suggests that the role of the market researcher is changing in the age of digital data. The marketing researcher of the future must fulfill the roles of being a social scientist and a storyteller . In both cases, although researchers may need to develop technical skills, it is also essential that they develop the ability to engage their clients, add value, and interpret data. Implications for industry and academia are discussed.